Exploring the potential cost-effectiveness and societal burden implications of screening for fracture risk in a UK general radiography setting - E. Söreskog; B. Lopez; T. Bean; P. Lewis; N. Ashley; J. Da Palma Lopes; R. Meertens; A. Ratcliffe (BMC Musculoskeletal Disorders)
Abstract Background Fragility fractures lead to considerable societal costs and individual suffering. Despite the availability of cost-effective treatments for high-risk patients, a significant treatment gap exists, with many high-risk individuals remaining unidentified and untreated. The aim of this study was to explore the potential cost-effectiveness and societal impact of opportunistic screening for fracture risk with IBEX Bone Health (BH), a software solution that provides bone mineral density from wrist radiographs, in a UK general radiography setting. Methods The study used a health economic model that compared the health outcomes and costs of screening with IBEX BH versus usual care for men and women aged 50 and older who had a forearm radiograph for any reason. The model incorporated data on fracture incidence, fracture risk reduction, mortality, quality of life, and fracture and treatment costs from published sources and Royal Cornwall Hospitals NHS Trust. Costs and health outcomes in terms of quality-adjusted life years (QALYs) were simulated over the remaining lifetime of patients. The analysis took the perspective of the National Health Service (NHS) and Personal Social Services in the UK. Results The results showed that screening with IBEX BH was associated with a gain of 0.013 QALYs and a cost saving of £109 per patient compared with usual care, making it a dominant (cost-saving) strategy. Sensitivity analyses confirmed the robustness of the results under various assumptions. Widespread adoption of IBEX BH in the NHS was estimated to save 8,066 QALYs and £65,930,555 in healthcare costs over the lifetime of patients visiting hospitals for wrist radiographs each year. Conclusions IBEX BH could be a cost-effective tool for early identification and prevention of fragility fractures in the UK, addressing the current challenges of low provision and access to fracture risk assessment and treatment.